Study of elastic system fibers in human gingiva - Walter Augusto Soares Machado; Eduardo Muniz Barreto Tinoco; Renata Castanheira Machado; Gerson Cotta-Pereira
Objective: To map the participation of the elastic system fibers of human gingiva. Methods: To conduct this study, fragments of human gingiva from ten individuals aged between 18 and 60 years, removed after periodontal surgery for prosthetic purposes, were analyzed by the histochemical and immuno-histochemical methods, to evaluate the participation of the elastic system fibers in this tissue. Results: The results demonstrated the presence of three type of elastic system fibers, that is to say, oxitalan, elaunin and elastic fibers,distributed as follows: 1) the oxitalan fibers form a network of thin fibers, located close to the basal membrane, at the level of the conjunctive tissue papillae; 2) elaunin fibers are found in close contact with the oxitalan fibers in the papillary and submaxillary regions, following the collagen fiber bundles; 3) a small quantity of elastic fibers were observed, dispersed throughout the deeper conjunctive tissue and around the blood vessels. Conclusion: The three types of elastic system fibers, that is, oxitalan, elaunin and elastic fibers are normal constituents of the extracellular matrixof human gingiva conjunctive tissue.